Regional University Marketing in Under-developed Regions - Robert Štefko; Miroslav Frankovský; Radovan Baèík (Contemporary Economics)
Specific approaches, in the field of the University marketing, are discussed with the higher intensity last decades. But the Universities established in underdeveloped regions have special position, function, possibilities, and specific needed activities. There are also many reasons for applying modified strategies and marketing tools in Slovak higher educational market. The study deals with main and dominant approaches in this area of managing of educational institutions in Slovak environment but the study also presents the results of the research. The sample of the research was selected from students of the Faculty of Management, University of Preöov, Slovak Republic. There was marketing product policy designed and mainly communications policy and image mainly analysed there. There are offered some suggestions for universities in the final part of the study.